ANALISIS KEUNTUNGAN PEDAGANG PENGUMPUL â€œKELAPA KUAHâ€ DI DESA TEWASEN KECAMATAN AMURANG BARAT - Exaudia Enggelina Rempowatu; Paulus Adrian Pangemanan; Grace Adonia Josefina Rumagit (AGRI-SOSIOEKONOMI, 2018)
The research aims to calculate the profit of coconut collector "Kelapa Kuah" in Tewasen Village, West Amurang Sub-district. This research was conducted for 3 months from April to June 2018. The method used in this study was the survey method with the technique of direct interviewing with coconut collector. The research result showed that the profit of the coconut collecting trader was Rp. 16.861.169 and R/C ratio was 1.18 which meant that the business of coconut collecting trader was economically profitable and could be maintained.*JNKD*.